Analisis Kelengkapan Formulir A (Evaluasi Awal MPP) Dan Formulir B (Catatan Implementasi) Pasien Rumah Sakit - Dicho Zhuhriano Yasli; Devid Leonard; Berly Nisa Srimayarti (Akademi Perekam dan Informasi Kesehatan Imelda, 2021)
Completeness of the Inpatient Examination Form is a problem that often causes complaints in several hospitals. The purpose of this study was to conduct a literature review related to the incomplete analysis of filling in form A, MPP Initial Evaluation and Form B Implementation Notes. The collection method is secondary data, the steps are determining keywords, exploration and title selection, reading articles that have not been eliminated. At that stage, the reference list of selected articles is reviewed to determine other related studies. The articles contained in the summary list The results of the literature review, namely, still found incompleteness in filling out medical record forms, the responsibilities and attitudes of officers in filling out medical record files can be said to be still not optimal. The human resources involved are still lacking, for example the assembling officer also serves the file preparation so that the assembly function is not optimal. Based on the literature review of several related articles, further research is needed on other causes of incompleteness in filling out medical record file forms and the obstacles experienced by doctors in filling out medical record files.